2018
DOI: 10.1096/fj.201700412rr
|View full text |Cite
|
Sign up to set email alerts
|

CaSR signaling down‐regulates AQP2 expressionviaa novel microRNA pathway in pendrin and NaCl cotransporter knockout mice

Abstract: High concentrations of urinary calcium counteract vasopressin action via the activation of the calcium-sensing receptor (CaSR) that is expressed in the luminal membrane of collecting duct cells, which impairs the trafficking of aquaporin-2 (AQP2). Pendrin/NaCl cotransporter double-knockout (dKO) mice display significant calcium wasting and develop severe volume depletion, despite increased circulating vasopressin levels. We hypothesized that the CaSR-mediated impairment of AQP2 expression/trafficking underlies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…Novel AQP-targeting therapies through modulation of microRNA (miRNA) function have recently been suggested (reviewed in 122). The possibility of using miRNA alone or in combination with other drugs to modulate the vasopressin–AQP2 pathway specifically provides new hints for AQP-based therapeutics 27, 123 . In this respect, the recent identification of miR-132 as a first miRNA target which blocks vasopressin gene expression has opened new avenues for drug development 124 .…”
Section: Discussionmentioning
confidence: 99%
“…Novel AQP-targeting therapies through modulation of microRNA (miRNA) function have recently been suggested (reviewed in 122). The possibility of using miRNA alone or in combination with other drugs to modulate the vasopressin–AQP2 pathway specifically provides new hints for AQP-based therapeutics 27, 123 . In this respect, the recent identification of miR-132 as a first miRNA target which blocks vasopressin gene expression has opened new avenues for drug development 124 .…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of AQP2 protein is regulated by transcription of the Aqp2 gene and translation, and post-translational modification of products, including ubiquitination and subsequent proteasomal and/or lysosomal degradation, which involve the actions of E3 ubiquitin-protein ligases (e.g., NEDD4 and CHIP) [43,4652]. In addition, microR-NAs (miRNA; e.g., miR-32 and miR-137) are important post-transcriptional modulators that regulate AQP2 protein abundance [53,54]. A recent study showed that miR-132 regulates hypothalamic AVP mRNA expression [55].…”
Section: Overview Of Arginine Vasopressin and Aquaporin-2mentioning
confidence: 99%
“…This theory that elevated concentration of calcium in urine counteract vasopressin action via the activation of CaSR expressed at luminal membrane of principal cells has been further validated in a mouse model double-knockout (dKO) for Pendrin/NaCl Cotransporter (NCC) [66], which display significant calcium wasting and severe volume depletion, despite high circulating vasopressin levels [67].…”
Section: Casr and Aqp2 Interplaymentioning
confidence: 99%
“…Moreover, inhibition of p38-MAPK caused a drastic decrease in AQP2-pS261, along with a nearly five-fold increase in total AQP2. Furthermore, in dKO mice, p38-MAPK inhibition results in a drastic reduction in ubiquitinated AQP2 that is paralleled by a strong increase in total AQP2 [66].…”
Section: Casr and Aqp2 Interplaymentioning
confidence: 99%